2011
DOI: 10.1093/nar/gkr562
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of transcription and splicing of syncytins, fusogenic glycoproteins of retroviral origin

Abstract: Syncytin-1 and -2, human fusogenic glycoproteins encoded by the env genes of the endogenous retroviral loci ERVWE1 and ERVFRDE1, respectively, contribute to the differentiation of multinucleated syncytiotrophoblast in chorionic villi. In non-trophoblastic cells, however, the expression of syncytins has to be suppressed to avoid potential pathogenic effects. We studied the epigenetic suppression of ERVWE1 and ERVFRDE1 5′-long terminal repeats by DNA methylation and chromatin modifications. Immunoprecipitation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 56 publications
3
45
0
Order By: Relevance
“…In contrast, few studies have looked at the interaction of HDACs with HERV LTRs. One study used ChIP to show that histone H3 acetylation was critical to the expression of HERV-W and HERV-FRD env in placental tissues, where they are known to have biological roles [30]. However, in non-placental tissues transcription is suppressed by histone H3 methylation and inefficient splicing [30].…”
Section: Higher Concentrations Of the Hdac Inhibitors Do Not Up-regulmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, few studies have looked at the interaction of HDACs with HERV LTRs. One study used ChIP to show that histone H3 acetylation was critical to the expression of HERV-W and HERV-FRD env in placental tissues, where they are known to have biological roles [30]. However, in non-placental tissues transcription is suppressed by histone H3 methylation and inefficient splicing [30].…”
Section: Higher Concentrations Of the Hdac Inhibitors Do Not Up-regulmentioning
confidence: 99%
“…One study used ChIP to show that histone H3 acetylation was critical to the expression of HERV-W and HERV-FRD env in placental tissues, where they are known to have biological roles [30]. However, in non-placental tissues transcription is suppressed by histone H3 methylation and inefficient splicing [30]. Histone H3 acetylation was detectable in a placental cell line but not in HeLa cells, corresponding to transcriptional activation in the placenta but suppression elsewhere.…”
Section: Higher Concentrations Of the Hdac Inhibitors Do Not Up-regulmentioning
confidence: 99%
“…The assay for the ERVWE1 locus previously described (17) was used to determine the levels of ERVWE1 exon transcripts. Assays described previously (26) were used to determine the levels of nonspliced and spliced ERVWE1 transcripts. Threshold cycle (C T ) values from the exponential phase of the qPCR amplification plot for each target transcript were normalized to those for the gene encoding ␤-actin (see reference 38).…”
Section: Cell Culture and Influenza A/wsn/33 Virus Infections Of Cultmentioning
confidence: 99%
“…In addition to tissue-restricted expression of transcription factors, CpG methylation (24,25) and histone modifications (26) contribute to repression of ERVWE1 and other HERV-W loci. An increasing body of literature suggests that viral infections can modify the methylation status of host DNA in cells of rat and human origin (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Expression of these fusogenic proteins is tightly restricted to placental trophoblast cells. It has been shown that these genes are silenced in somatic cells by DNA methylation of CpGs within 5' long terminal repeats (LTRs) (Matousková et al, 2006;Trejbalová et al, 2011). Aberrant methylation of these 5' LTRs in trophoblast cells might lead to the inadequate formation of the syncytiotrophoblast and a malfunctioning placenta.…”
Section: Gene Regulation By Dna Methylation In the Trophoblast Cell Lmentioning
confidence: 99%